Saka Guru dan Atap Tumpang Tiga : Keunikan Arsitektur Masjid Agung Demak - Ayu Ifrochah; Ummi Roro Kusuma Dewi; Miftakhul Khairi (Abstrak : Jurnal Kajian Ilmu seni, Media dan Desain, 2025)
The Great Mosque of Demak is one of the most significant Islamic historical heritages on the island of Java. Built in the 15th century by Raden Fatah and Walisongo, this mosque symbolizes the beginning of the glory of Islam in the archipelago. Its distinctive architecture depicts the acculturation of Javanese and Islamic culture, with unique elements such as the three-tiered pyramid roof which symbolizes faith, Islam and ihsan, as well as the "Saka Guru," the four main pillars of the mosque which have deep symbolic value. Saka Guru, including Saka Tatal which was assembled from small pieces of wood by Sunan Kalijaga, reflects the values of unity, strength and creativity within limitations. This tradition shows the important role of the Walisongo in spreading Islam as well as introducing mosque architecture that integrates local traditional and religious values. This research uses a qualitative descriptive method, with data collection through expert interviews, literature studies and field surveys. The results of the analysis reveal that Saka Guru not only supports the physical structure of the mosque but also represents the spiritual and cultural values passed down to the people of Demak. In this way, the Great Mosque of Demak has become a symbol of the combination of culture, spirituality and architecture which continues to be relevant today.